Neuroticism in child sex offenders and its association with sexual dysfunctions, cognitive distortions, and psychological complaints. (September 2017) - Boillat, Coralie; Deuring, Gunnar; Pflueger, Marlon O.; Graf, Marc; Rosburg, Timm
Abstract: Studies in child sex offenders (CSO) often report deviant personality characteristics. In our study, we investigated neuroticism in CSO and tested the hypothesis that CSO with high neuroticism show more serious abuse behavior and are more likely to exhibit sexual dysfunction and cognitive distortions, as compared to CSO with low neuroticism. A sample of 40 CSO (both child sexual abusers and child sexual material users) was split into two subsamples based on their neuroticism scores, obtained by the NEO-Personality Inventory-Revised (NEO-PI-R) questionnaire. Subsequently, we compared their scores in the Multiphasic Sex Inventory (MSI) questionnaire and Symptom Checklist-90-Revised (SCL-90-R). Our results show that CSO exhibited higher levels of neuroticism than controls, but were still in the normal range. In CSO, neuroticism was associated with sexual dysfunction and cognitive distortions, rather than with more severe abuse behavior. Moreover, neuroticism in this group was linked to a broad range of psychological problems and psychopathological symptoms, such as somatization or anxiety. Our findings suggest that neuroticism even below the level of personality disorder is associated with a broader range of psychological problems in CSO, which should be addressed in therapy.